DYNAMIC SCENARIOS IN FINANCE AND MANAGEMENT, LOOKING TO 2024 - Alejandro Torres Mussatto; Eric Salinas Mayne (European Scientific Journal, ESJ, 2014)
This research aims to study management skills in dynamic scenarios, taking as reference the theories: Dynamic – Systems (M. Vera, 2011), Fractal Catalysis (Davia, 2006) and Intelligence and Reason (X. Zubiri, 1983).The overall aim of this study is to identify the dynamic financial scenarios and management up to the year 2024 and to determine the profile of management skills suitable to these scenarios. The specific aims consist in: identifying the dynamic scenarios in finance and management with a projection to year 2024; identifying the main characteristics of the current financial-oriented management skills and management profiles; and determining a profile management with financial guidance skills and relevant management in dynamic scenarios. The methodology used applies an observational analytical design with a qualitative approach. The results indicate that professional scenarios used in profiles of current management skills are static and not dynamic;therefore, we can conclude that from the perspective of the national and international financial scenarios and the scenarios of financial experts up to 2024 show significant changes with an overall positive trend in the area of finance and management; more dynamics; and the need of better and more competent professionals. They also indicate that professionals need to develop new and better skills, use new strategies and ways to learn, and have to face difficulties in the development of its work related to the dynamics of the financial and economic system. Its functions will be developed with various new forms of work,such as in an environment of greater complexity, control, and automation. Their work will be more demanding, interdisciplinary, and within complex environments; it will require international experience.